2010
DOI: 10.1007/s12283-010-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of high-speed badminton racket kinematics by motion capture

Abstract: The kinematics of a badminton racket during a smash stroke was observed in this study with the purpose of investigating stroke dynamics and racket behaviour. Motion capture measurements of the racket during several smash strokes performed by three players of different skill levels indicated a clear increase in racket velocity at impact with increasing skill level. Variations between translational and rotational contributions to the impact speed could also be seen between the players. The advanced player produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 1 publication
3
16
2
Order By: Relevance
“…(4) Lastly, the mechanism of the racket deflection influences the terminal velocity of the shuttlecock (Kwan et al 2010). …”
Section: Resultsmentioning
confidence: 99%
“…(4) Lastly, the mechanism of the racket deflection influences the terminal velocity of the shuttlecock (Kwan et al 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Kwan, Andersen, Cheng, Tang, and Rasmussen [8] use a motion capture system to measure motion signals of a badminton racket, and the system is used to assess the performance of players in different skill levels. Jainter and Gawin [9] utilize three sensor nodes placed on the right upper arm, right lower arm, and racket to explore the relativities among racket speed, shuttle ball speed, and arm speed when a badminton smash is performed.…”
Section: Introductionmentioning
confidence: 99%
“…The processed results are presented in Table 20. Values generally agreed with the past works that were done for motion capture of badminton racket smash stroke, as seen in [110,111]. Literatures have shown that top players are capable of using the elastic deflection of badminton racket to achieve a higher tip speed [112][113][114].…”
Section: Motion Analysis Of Racket Speedsupporting
confidence: 86%